2021
DOI: 10.1038/s41416-021-01440-8
|View full text |Cite
|
Sign up to set email alerts
|

New clinical and biological insights from the international TARGIT-A randomised trial of targeted intraoperative radiotherapy during lumpectomy for breast cancer

Abstract: Background The TARGIT-A trial reported risk-adapted targeted intraoperative radiotherapy (TARGIT-IORT) during lumpectomy for breast cancer to be as effective as whole-breast external beam radiotherapy (EBRT). Here, we present further detailed analyses. Methods In total, 2298 women (≥45 years, invasive ductal carcinoma ≤3.5 cm, cN0–N1) were randomised. We investigated the impact of tumour size, grade, ER, PgR, HER2 and lymph node status on local recurrence-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 25 publications
1
41
0
2
Order By: Relevance
“…The 2.1% IBTR rate is similar to the TARGIT-A trial, which demonstrated a 2.11% rate of IBTR with a 5-year complete follow-up (9). This is despite 40% of patients having a change in their ASTRO APBI CG suitability group pre to post-operatively and consistent with more recent subgroup analysis from the TARGIT-A trial suggesting that there is no difference in the local control achieved by TARGIT-IORT and EBRT, irrespective of tumor size or subtype (12). Similar to the TARGIT-A trial 17.3% of patients received additional WBI, most of whom were classified as unsuitable postoperatively.…”
Section: Discussionsupporting
confidence: 85%
“…The 2.1% IBTR rate is similar to the TARGIT-A trial, which demonstrated a 2.11% rate of IBTR with a 5-year complete follow-up (9). This is despite 40% of patients having a change in their ASTRO APBI CG suitability group pre to post-operatively and consistent with more recent subgroup analysis from the TARGIT-A trial suggesting that there is no difference in the local control achieved by TARGIT-IORT and EBRT, irrespective of tumor size or subtype (12). Similar to the TARGIT-A trial 17.3% of patients received additional WBI, most of whom were classified as unsuitable postoperatively.…”
Section: Discussionsupporting
confidence: 85%
“…Recently reported data from the TARGIT-A trial, a risk-adapted targeted intraoperative radiotherapy (TARGIT-IORT) during lumpectomy for breast cancer, showed IORT to be as effective as whole-breast external beam radiotherapy (EBRT) [82]. Vaidya et al presented further detailed analyses of the trial and concluded that TARGIT-IORT is as effective as EBRT in all subgroups for local recurrence-free survival (HR 0.75; 95% CI 0.57-1.003; p = 0.052) and overall survival (HR 0.96; 95% CI 0.68-1.35; p = 0.80) [83]. One of the striking findings was that unlike EBRT where local recurrence was a powerful predictor of distant metastases, breast cancer mortality and overall mortality, local recurrence following IORT did not have worse survival outcomes, suggesting possible action at a distance.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…An immediate downregulation of surgically induced tumor-growth factors could potentially yield improved disease-control outcomes, overcoming a temporal miss factor ( 23 25 ). Recent data have suggested an improvement in breast cancer mortality for those patients undergoing IORT; nevertheless, different confusing factors might be associated with these differences and further research is warranted to confirm this statement ( 13 , 26 ). An interesting feature related to this cohort was the time elapsed between IORT and EBRT start.…”
Section: Discussionmentioning
confidence: 98%